FORMULASI SIRUP EKSTRAK DAUN LEGUNDI (Vitex trifolia L.) - Lalita Lisprayatna; Yosi Bayu Murti; T. Nanda Saifullah Sulaiman (Majalah Obat Tradisional, 2012)
Daun legundi (Vitex trifolia) has been used by Indonesian people as antiasthma. This research aims to produced the good quality syrup of extract of daun legundi and also to evaluate the relative level change of viteksikarpin in syrup after formulation. Syrup of extract of daun legundi was made for 4 formulas of variation of propylene glycol (PG) level. Formula 1 (PG 11%), formula 2(PG 12%), formula 3 (PG 13%) and control (without PG). Each formula was tested for physical characteristic (organoleptic, viscosity, time of flow, flavor test), relative level of viteksikarpin against extract. The result showed that increase of propylene glycol level was increased the viscosity syrup and time of flow while the percentage of relative level of viteksikarpin against extract was decreased. In this research, formula 1 (PG 11%) was the selected formula because it has a good flavor and appearance, less viscosity, least precipitate, highest relative level of viteksikarpin and acceptable in the market.